2013
DOI: 10.1038/onc.2013.359
|View full text |Cite
|
Sign up to set email alerts
|

ASCL1 and RET expression defines a clinically relevant subgroup of lung adenocarcinoma characterized by neuroendocrine differentiation

Abstract: ASCL1 is an important regulatory transcription factor in pulmonary neuroendocrine (NE) cell development, but its value as a biomarker of NE differentiation in lung adenocarcinoma (AD) and as a potential prognostic biomarker remains unclear. We examined ASCL1 expression in lung cancer samples of varied histologic subtype, clinical outcome and smoking status and compared with expression of traditional NE markers. ASCL1 mRNA expression was found almost exclusively in smokers with AD, in contrast to non-smokers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
67
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 31 publications
2
67
0
Order By: Relevance
“…It is overexpressed in a variety of tumors, including breast, lung, and pancreas carcinomas (51)(52)(53). Altered expression of hnRNP-A2/B1 has also been reported during lung carcinogenesis where hASH1 seems to be involved (54,55). Histochemical mapping of hnRNP-A2/B1 suggested a function in post-transcriptional regulation of neurons in the cerebral cortex and hippocampus in response to ischemia-reperfusion injury (56).…”
Section: Discussionmentioning
confidence: 99%
“…It is overexpressed in a variety of tumors, including breast, lung, and pancreas carcinomas (51)(52)(53). Altered expression of hnRNP-A2/B1 has also been reported during lung carcinogenesis where hASH1 seems to be involved (54,55). Histochemical mapping of hnRNP-A2/B1 suggested a function in post-transcriptional regulation of neurons in the cerebral cortex and hippocampus in response to ischemia-reperfusion injury (56).…”
Section: Discussionmentioning
confidence: 99%
“…A minority (10%) of ACC exhibited NETest levels > 40%. This may reflect the well-described phenomenon of neuroendocrine differentiation in highly aggressive lung tumors [36, 37] and likely detects a tissue-­derived neuroendocrine phenotype. Recent publications have identified significant cellular heterogeneity in lung neoplasia including NE differentiation in ∼10% of ACC and reclassification of 5% of SCCs as LCNEC [36, 38, 39].…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with that of the research of lung adenocarcinoma. 5 Additionally, ASCL1 was overexpressed in laryngeal cancer with high migration level, but profoundly expressed weakly in laryngeal cancer with low migration level, suggesting that ASCL1 may be of a tumor-accelerating property. 24 Besides, multivariate analysis showed that ASCL1 protein was an important independent prognostic factor for overall survival, and ASCL1 could be used as a new predictor of the prognosis of cases with laryngeal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…5 Some studies indicated that the abnormal expression and function of ASCL1 protein are crucial to the occurrence of human cancers [6][7][8][9][10][11][12] of many kinds, in which increased ASCL1 expression levels have been detected, and silencing ASCL1 expression could suppress the proliferation of both cancer 6,7,10 and neuroendocrine tumor. 5,13,14 And some report that suppression of ASCL1 expression by RNA interference could lead to cellcycle procession as well as cell differentiation and apoptosis and inhibit growth in vitro in an ASCL1 expression-dependent manner. 11,15,16 It was found that ASCL1 is also involved in the migration of cancer cells in various carcinoma cell lines such as oral squamous cell carcinoma line 17 and lung cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%